The Role of Gender Differences in Partnering and Re-partnering for Gender Differences in Completed Fertility - Andersson Linus (SPRINGER, 2025)
Individuals increasingly enter a series of relationships during their reproductive years. As births in higher-order unions increase, fertility becomes partially contingent on re-partnering. Previous research suggests that men re-partner at higher rates than women. This study analyzes whether gender differences in partnering and re-partnering influence gender differences in cohort fertility. We use Finnish register data on all births, marriages, and cohabitations between the ages of 18 and 47 over four full birth cohorts. The gender differences in cohort fertility rate are decomposed into components due to birth rate differences and a compositional component owing to gender differences in the share partnered and re-partnered. We observe no impact of "re-partnering premium" on male fertility. Men have marginally higher re-partnering rates at older ages, when birth rates are low, whereas women have higher rates of partnering and re-partnering at prime childbearing ages. This compositional effect drives a "partnering" advantage for female fertility. This connection between gender differences in partnering and cohort fertility is true across educational levels.